Simultaneous Lymphatic and Alveolar Leak: High-Output Non-Traumatic Chylothorax with Bilateral Fluidopneumothorax and Pneumomediastinum in a 27-Year-Old Woman Treated by Thoracoscopic Duct Ligation and Mechanical Pleurodesis - Tjokorda Istri Anom Saturti; I Gusti Agung Dwi Putri Anjani; Gede Vivekananda Rusdi; I G Mahapraja Divasta; I Wayan Tegar Raharja Ariawan (Phlox Institute: Indonesian Medical Research Organization, 2026)
Background: Chylothorax accounts for a small minority of pleural effusions, and the non-traumatic form is rarer still, usually indolent and usually low output. The simultaneous occurrence of high-output chylothorax and a spontaneous air-leak syndrome in an immunocompetent young adult has not been described. Objective: To report such a case, to quantify the metabolic and immunological cost of the leak, and to argue that a single mechanical trigger can breach the alveolar and the lymphatic conduits together. Case presentation: A 27-year-old woman with no trauma, thoracic surgery or malignancy developed progressive dyspnoea and recurrent massive pleural effusion requiring three thoracenteses, approximately 5,000 mL in 11 days. Tube thoracostomy then drained about 2,500 mL of serosanguineous, milky-pink fluid on the first day. Pleural fluid triglycerides were 1,774 mg/dL with cholesterol 130 mg/dL, a ratio of 13.6, lymphocyte predominance and a positive Rivalta test. Computed tomography showed bilateral fluidopneumothorax, pneumomediastinum, extensive subcutaneous emphysema and bilateral pneumonia, although lung sliding had been preserved bilaterally on admission ultrasonography. Lymphopenia of 0.63 ×109/L, albumin of 2.20 g/dL, rising haemoglobin and deterioration to pH 7.33 with PaO2 52 mmHg accompanied a daily loss of approximately 44 g of triglyceride. Thoracoscopic duct ligation with mechanical pleurodesis reduced drainage to 180–250 mL/day and the patient was discharged on day 28. Conclusion: High output does not imply trauma, and a non-traumatic cause does not imply an indolent course. Failure of conservative treatment is better defined by the metabolic and immunological ledger than by drainage volume alone.